Legal Analysis of the Government's Role in Allocating Land for Farmers to Provide Legal Certainty : Research Study in Batam City - Rudy Tarigan; Soerya Respationo; Parameshwara Parameshwara; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Batam City, as a rapidly growing industrial center, faces major challenges in allocating agricultural land for farmers who need legal certainty over the land they manage. The background of the problem in this study is the conflict of interest between industrial development and the need for agricultural land protection, which often sacrifices farmers' rights and causes legal uncertainty. The purpose of this study is to analyze the role of the government in allocating land for farmers in Batam City and to provide policy recommendations that can increase legal certainty over agricultural land. The research method used is a normative and empirical juridical approach, which includes an analysis of relevant laws and regulations such as Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land, and Law Number 19 of 2013 concerning the Protection and Empowerment of Farmers. Primary data was collected through interviews with farmers, government officials, and other stakeholders, while secondary data was obtained from legal literature, policy documents, and previous case studies.The results of the study show that the implementation of land allocation for farmers in Batam City has not been optimal. Farmers often do not get adequate legal certainty because the allocated land can be revoked at any time by the government for the benefit of industrial development. The main obstacles identified include conflicts of interest between economic development and agricultural land protection, lack of legal certainty, weak coordination and oversight, development and urbanization pressures, and lack of supporting infrastructure. As a suggestion, this study recommends that the Batam City Government develop a balanced and inclusive spatial planning policy, accelerate the land certification process for farmers, improve coordination between institutions, and invest in agricultural infrastructure development. In addition, farmers are expected to strengthen their organizations to advocate for their rights, while the people of Batam City need to actively participate in the process of land use planning and monitoring to ensure sustainable and equitable development.